Association between school bullying victimization and self-harm in a sample of Chinese children and adolescents: The mediating role of perceived social support - Che, Yusan; Lu, Jin; Fang, Die; Ran, Hailiang; Wang, Sifan; Liang, Xuemeng; Sun, Hao; Peng, Junwei; Chen, Lin; Xiao, Yuanyuan (Frontiers in Public Health, 2022)
Background Studies indicated that bullying victimization (BV) is an important risk factor for self-harm in children and adolescents. However, it is unclear whether perceived social support significantly mediates this association. This study aimed to examine the association between BV and self-harm, with a particular focus on the mediating role of perceived social support. Methods A population-based cross-sectional study of 4,627 Chinese students aged from 10 to 17 years was conducted in southwestern China Yunnan province. A two-stage simple random cluster sampling method was used to choose study subjects. The adjusted associations between school BV, perceived social support, and self-harm were examined by using the multivariate logistic regression models. The mediation of perceived social support in the association between BV and self-harm was evaluated by using a path model. Results After controlling potential covariates, BV was associated with a prevalence of increased self-harm, with an adjusted odds ratio of 1.90 (95% CI: 1.57, 2.32). Among all sources of perceived social support, only parental support played a prominent mediating role in the association between BV and self-harm, accounting for 20.73% of the explained variance. The mediation of parental support was comparable between boys and girls. As for different types of bullying victimization, path analyses indicated that only the association between physical victimization and self-harm was significantly mediated by parental support. Conclusion Our study results highlighted the promising interventional benefit of parental support in BV-associated self-harm risk for children and adolescents. For victims of bullying, especially physical bullying, promoting parental support might be effective in reducing self-harm risk. Longitudinal studies are warranted to further corroborate these findings.